Populism in new media: the online presidential campaign discourse in Indonesia - Santoso, Didik Haryadi; Jamaluddin Aziz; Pawito; Utari, Prahastiwi; Kartono, Drajat Tri (Penerbit Universiti Kebangsaan Malaysia, 2020)
Populism is often seen as a tactic, strategy and method of campaigning in political communication that exploits political discourse. Populism plays a vital role in Indonesia’s 2019 presidential election. Various research has been carried out to understand the practice of populism. However, few have explained the way social media and online news in populist communication practices relate to the discourse of the online presidential campaign. This research aims to understand the pattern of the use of populist discourse in Indonesia’s 2019 presidential election in online news and social media. The study employed Fairclough’s Critical Discourse Analysis (CDA) that focuses on social identity construction and the relation of populist discourse practices. Data for the study were obtained from online news from January 15 to February 14, 2019. A total of 81 news articles from online news and 576,782 entries that are disseminated in Facebook, Twitter, Instagram, and YouTube were analyzed by using Nvivo and web crawlers. This research finds that, first, political discourse and populist discourse are amplified by online news coverage and extended in the social media; second, online news does not engage in producing populist discourse but echoes the populist discourse by citing politician’s populist utterance. In conclusion, populist keywords and concepts like infrastructure, food, energy, and radical become a hegemonic discourse in Indonesia’s 2019 presidential election. There are two important contributions of this study on populist discourse in Indonesia’s 2019 election campaign. One, the knowledge of the pattern of the distributionof populist discourse. Two, the understanding about the use of populist discourse in social media and online news.